2021
DOI: 10.1371/journal.pone.0257852
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic restrictions continuously impact on physical activity in adults with cystic fibrosis

Abstract: Background We have recently reported reduced physical activity (PA) in people with cystic fibrosis (pwCF) with and without lung transplantation (LTX) during a 6-week stringent lockdown in Switzerland. This follow-up study explores the impact of coronavirus-2019 disease (COVID-19) related pandemic restrictions on individuals’ therapy regimens and health-related aspects in pwCF. Methods We conducted a cross-sectional web-based national survey in Spring 2021. The survey included questions on daily PA, airway cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…When comparing changes in lifestyle behaviours from before to during the COVID-19 pandemic, our results show, based on the effect sizes, a small but significant decrease in VPA and a large increase in SED. These results are consistent with other studies suggesting a decrease in MPA and VPA in the general population ( Lesser and Nienhuis, 2020 , Wunsch et al, 2022 ) and in immunosuppressed populations with lupus, rheumatoid arthritis, or cystic fibrosis ( Ammitzbøll et al, 2021 , Radtke et al, 2021 ) during the COVID-19 pandemic. In two studies among immunosuppressed individuals, 45–46% of participants reported being less active since the start of the pandemic ( Ammitzbøll et al, 2021 , Radtke et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When comparing changes in lifestyle behaviours from before to during the COVID-19 pandemic, our results show, based on the effect sizes, a small but significant decrease in VPA and a large increase in SED. These results are consistent with other studies suggesting a decrease in MPA and VPA in the general population ( Lesser and Nienhuis, 2020 , Wunsch et al, 2022 ) and in immunosuppressed populations with lupus, rheumatoid arthritis, or cystic fibrosis ( Ammitzbøll et al, 2021 , Radtke et al, 2021 ) during the COVID-19 pandemic. In two studies among immunosuppressed individuals, 45–46% of participants reported being less active since the start of the pandemic ( Ammitzbøll et al, 2021 , Radtke et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is unclear how immunosuppressed individuals’ lifestyle behaviours are affected by stressful life events such as COVID-19 pandemic and its related PSD measures. Immunosuppressed individuals were given strict instructions regarding self-isolation and avoidance of social contact given their increased risk of severe complications due to COVID-19 ( Banerjee et al, 2020 , Bhoori et al, 2020 ), which represented additional barriers to maintain healthy lifestyle behaviours during the pandemic ( Ammitzbøll et al, 2021 , Lupi et al, 2020 , Radtke et al, 2021 , Radtke et al, 2020 ). These behaviours likely extend to close relatives of immunosuppressed individuals as they might adopt stricter PSD measures to protect their loved ones ( Chan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We think that during lockdown, despite the fact that most of our population reported an unchanged diet, patients had greater adherence to therapy, assuming that they took their pancreatic enzymes more regularly and did not skip meals. In addition, although the population similarly stated reduced physical activity in another study, most patients reported better adherence to respiratory physical therapy [15].…”
Section: Discussionmentioning
confidence: 86%
“…Pulmonary exacerbations are associated with increased energy expenditure [ 21 ], therefore, reduced incidence of pulmonary exacerbations in the post-index period may have positively influenced BMI. Another potential explanation for increased BMI is reduced levels of physical activity during the pandemic [ 22 ] and other pandemic related behaviours such as increased snacking on energy dense foods [ 23 ]. An alternative measure such as fat free mass index would be helpful in elucidating the impact of the pandemic on nutritional status, however, fat free mass index is not a routinely collected clinical measure.…”
Section: Discussionmentioning
confidence: 99%